Mennonites in Canada, 1939-1970 : a People Transformed. - Regehr, T. D. (Mennonites in Canada., 1996)
T.D. Regehr shows how the Second World War challenged the pacifist views of Mennonites and created a population more aware of events, problems, and opportunities for Christian service and personal advancement in the world beyond their traditional rural communities.